The Effect of Using Reading Aloud Technique in Improving Students’ Reading Comprehension Achievement at SMP Negeri 19 Palembang - Herlina, Dini; Angraini, Nike; Angraini, Dita Rizki (Indo-MathEdu Intellectuals Journal, 2024)
Students' reading comprehension in Indonesia was feeble because many students were reluctant to read. Therefore, this study used a reading-aloud strategy to improve reading comprehension in grade 7 students at SMP Negeri 19 Palembang. The research design used a quasi-experimental design, involving two groups of 7th-grade students: an experimental group receiving the reading-aloud intervention and a control group not. The samples in this study were classes VII9 and VII7, totaling 33 students per class. Pre-tests and post-tests were administered to assess reading comprehension levels. The results of this research were (1) there was an improvement in students' reading comprehension achievement after using the reading aloud strategy. (2) There was significant improvement in each aspect of reading comprehension. (3) There was a contribution of each aspect to reading comprehension achievement. (4) There was a significant mean difference between the students who were taught by using the reading-aloud strategy and those who were not taught by the reading-aloud strategy. Based on the results of this research, the reading-aloud strategy was effective in improving students' reading comprehension achievement and enhancing various aspects of reading among the seventh-grade students of SMP Negeri 19 Palembang